Growth and retreat of the last British–Irish ice sheet, 31 000 to 15 000 years ago : the BRITICE‐CHRONO reconstruction - Clark, Chris D.; Ely, Jeremy C.; Hindmarsh, Richard C. A.; Bradley, Sarah; Ignéczi, Adam; Fabel, Derek; Ó Cofaigh, Colm; Chiverrell, Richard C.; Scourse, James; Benetti, Sara; Bradwell, Tom; Evans, David J. A.; et al. (Boreas, 2022)
Funding information: This work was funded by the Natural Environment Research Council consortium grant BRITICE-CHRONO NE/J009768/1 and by the NERC Radio- carbon Facility and the NERC Cosmogenic Isotope Analysis Facility. The project benefited from the PalGlac team of researchers with funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation programme to CDC (Grant Agreement No. 787263) and supporting SB and AI. JCE acknowledges support from a NERC independent fellowship award (NE/R014574/1). We thank the PISM team of ice-sheet modellers and Evan Gowan for ICESHEET, and note that the development of PISM was supported by NSF grants PLR- 1603799 and PLR-1644277 and NASA grant NNX17AG65G. DP acknowledges funding from the Italian PNRA project IPY GLAMAR (grant number 2009/A2.15), and from the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement no. 656821 (project SEAGAS). The BRITICE‐CHRONO consortium of researchers undertook a dating programme to constrain the timing of advance, maximum extent and retreat of the British–Irish Ice Sheet between 31 000 and 15 000 years before present. The dating campaign across Ireland and Britain and their continental shelves, and across the North Sea included 1500 days of field investigation yielding 18 000 km of marine geophysical data, 377 cores of sea floor sediments, and geomorphological and stratigraphical information at 121 sites on land; generating 690 new geochronometric ages. These findings are reported in 28 publications including synthesis into eight transect reconstructions. Here we build ice sheet‐wide reconstructions consistent with these findings and using retreat patterns and dates for the inter‐transect areas. Two reconstructions are presented, a wholly empirical version and a version that combines modelling with the new empirical evidence. Palaeoglaciological maps of ice extent, thickness, velocity, and flow geometry at thousand‐year timesteps are ...